Developing the Students' Reading Comprehension through Interactive Approaches by Using Short Stories (An Experimental Research at South Aceh Polytechnic) - Asmaidi; Hasbaini; Amsar Yunan (LPPM Politeknik Aceh Selatan, 2020)
This research was conducted to see the effectiveness of using short stories in teaching reading comprehension. The teaching model was used an interactive approach to be developed the reading skills of second semester students at the Department of Computer Engineering, South Aceh Polytechnic. The reading ability of students was explored and to be found the right teaching model, then the aspects of the ability to be seen was understanding the meaning of words, sentence intentions, information, problems, opinions, recommendations, sentence structure, analysis and communication and student responses after the application of the teaching model in the classroom. After treatment, there was an increase in students' reading comprehension skills especially in the experimental class after using short story teaching materials with interactive approach teaching models to obtain an average value of pre-test = 55, and post-test = 77.67. Whereas in the control class only got a pre-test value = 49,64 and post-test = 67,86. Then there was a significant difference in the scores of the two classes in the post-test scores (77,67-67,86) namely 9,81. Meanwhile, from questionnaire data, 87% of students responded very well and the remaining 13% responded well to the use of short stories with interactive approach teaching models. As well as answering enough options and less as much as 0%. From the responded above, which has helped develop student confidence, collaboration, self-ability and group work. Of course this research was far from perfection and needs to be improved in the future with other teaching methods, while still providing motivation to students to continue to be improved their learning, especially reading skills. So from the results of this simple study it can be recommended that, the use of short stories in teaching comprehension reading with interactive approach models got a significant increase in students' ability in reading comprehension than conventional learning models.